2007
DOI: 10.1073/pnas.0610064104
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evolution of affinity and flexibility in the immune system

Abstract: The immune system responds to the introduction of foreign antigens by rapidly evolving antibodies with increasing affinity for the antigen (i.e., maturation). To investigate the factors that control this process at the molecular level, we have assessed the changes in flexibility that accompany ligand binding at four stages of maturation in the 4-4-20 antibody. Our studies, based on molecular dynamics, indicate that increased affinity for the target ligand is associated with a decreased entropic cost to binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
126
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(134 citation statements)
references
References 45 publications
(55 reference statements)
7
126
0
Order By: Relevance
“…The observed conformational variations in germline Ab-combining sites are consistent with the predictions based on thermodynamic studies and molecular dynamics simulations (5,33). On the basis of energy considerations, the conformations adopted by CDRH3 cannot represent a continuum of conformational space but, rather, correspond to a finite number of discrete states.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The observed conformational variations in germline Ab-combining sites are consistent with the predictions based on thermodynamic studies and molecular dynamics simulations (5,33). On the basis of energy considerations, the conformations adopted by CDRH3 cannot represent a continuum of conformational space but, rather, correspond to a finite number of discrete states.…”
Section: Discussionsupporting
confidence: 72%
“…Six structures of the germline mAb BBE6.12H3, in different chemical environments, quantitatively define the conformational repertoire of the CDRs, providing a rich data set for examining paratope topologies, although thermodynamic and computational studies have provided interesting clues regarding the generation of diversity in primary Ab response (5,19,33,34). Similarly, crystallographic and kinetic analyses of mature Abs SPE7 and NQ22/61.1, respectively, have also suggested conformational isomerism (7,19).…”
Section: Discussionmentioning
confidence: 99%
“…The results of the current study, in which both the vibrational and conformational terms were measured, indicate that the approximation is not necessarily valid because the vibrational term was found to be the more dominant factor. Similar results have been reported by recent studies that suggested a narrowing of the energy landscape or the limitation of the flexibility of side-chain conformations contributes significantly to decrease in entropy upon association (17,20).…”
supporting
confidence: 79%
“…During antibody affinity maturation through somatic mutation in vivo, this flexibility is thought to be reduced leading to increased affinity and specificity. [4][5][6] With this in mind, one possibility is that conformational flexibility may have been introduced upon grafting the LD1 CDRs into the new human framework such that new interactions with C3d were enabled. Thus, rather than altering a direct interaction with C3 through affinity maturation, the changes made to CDR-H2 may have restricted the flexibility of this loop in a way that limited its interaction to FGFR4.…”
Section: Discussionmentioning
confidence: 99%